Photoacoustic tomography system based on Diode Laser to Imaging of some types of materials - Mitrayana Mitrayana; Dara Cynthia Nur Cahyani; Mirza Satriawan (Journal of Physics: Theories and Applications, 2020)
Photoacoustic tomography imaging research has been conducted to distinguish several types of materials. The photoacoustic tomography imaging system used in this study uses a diode laser as a source of radiation and a condenser microphone as a detection tool. The sample is a combination of two types of materials, namely plasticine + iron wire, plasticine + cardboard, plasticine + mica plastic, and mica plastic + cardboard. Optimum setting of laser modulation frequency and duty cycle system to distinguish images from plasticine samples + iron wire and plasticine + cardboard, i.e., 19 kHz and 50%, while to recognize images from plasticine samples + mica plastic and mica plastic + cardboard, which is 19.5 kHz and 50%. The photoacoustic tomography image system used can detect and image the sample clearly, the striking color difference between one material, and another shows the difference in sound intensity.